Antibacterial Modes of Herbal Flavonoids Combat Resistant Bacteria - Song, Lianyu; Hu, Xin; Ren, Xiaomin; Liu, Jing; Liu, Xiaoye (Frontiers in Pharmacology, 2022)
The increasing dissemination of multidrug resistant (MDR) bacterial infections endangers the global public health. How to develop the effective antibacterial agents against resistant bacteria is becoming one of the most urgent demands to solve the drug resistance crisis. Traditional Chinese medicines (TCM) with multi-target antibacterial actions are emerging arsenal to overcome the antibacterial resistance. Base on the innovative concept of organic wholeness and syndrome differentiation on TCM on antibacterial therapies is encouraging. Herein, advances on flavonoid compounds of heat-clearing Chinese medicine exhibit the potential prospect for the therapy of resistant bacteria. In this review, we focus on the antibacterial modes of herbal flavonoids. Additionally, we overviewed the targets of flavonoid compounds and divide into direct-acting antibacterial compounds (DACs) and host-acting antibacterial compounds (HACs) based on their modes of action. We also discuss the associated functional groups of flavonoid compounds and highlight recent pharmacological activities against diverse resistant bacteria to provide the candidate drugs for the clinical infection.